1958
DOI: 10.1002/lipi.19580601007
|View full text |Cite
|
Sign up to set email alerts
|

Umesterungen auf dem Fettgebiet I: Theoretische Grundlagen und Schrifttum · Die Hydrier‐Umesterung

Abstract: stanz werden analytisch genau eingewogen, in 40 ml Benzol und 10ml Aceton gelost, auf 60°C erwarmt und ebenfalls eingefiillt. Zweckmafiig wird zuvor der Siulen-Aufsatz entfernt. Anmerkung I: Selbstverstandlich richten sich die anzuwendenden Losemittel nach dem zu trennenden Produkt. Auch Methanol oder die anderen oben angefuhrten Aktivatoren konnen in geringer Konzentration verwendet werden. Nun werden der Saulenkopf und das eingebaute Mittelrohr mit warmem 20 Vol.O/o Aktivator enthaltendem Losemittel sorgfalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1960
1960
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Several authors mention that the amount of FAME found in the interesterification product is always equivalent to the amount of sodium methanolate that has been added. [ 4,5 ] The “enolate” mechanism can easily explain this observation because all methanol present, whether resulting from hydrolysis of sodium methanolate or from formation of the glycerolate anion, will react with an enolate anion and produce a FAME. Another observation is that catalyst inactivation by water forms an amount of soap that is also equivalent to the amount of sodium methanolate. [ 6 ] The “explanation” that the sodium hydroxide formed when the sodium glycerolate reacts with water, would then saponify triglycerides and form an equivalent amount of soaps is most unlikely.…”
Section: Interesterificationmentioning
confidence: 99%
“…Several authors mention that the amount of FAME found in the interesterification product is always equivalent to the amount of sodium methanolate that has been added. [ 4,5 ] The “enolate” mechanism can easily explain this observation because all methanol present, whether resulting from hydrolysis of sodium methanolate or from formation of the glycerolate anion, will react with an enolate anion and produce a FAME. Another observation is that catalyst inactivation by water forms an amount of soap that is also equivalent to the amount of sodium methanolate. [ 6 ] The “explanation” that the sodium hydroxide formed when the sodium glycerolate reacts with water, would then saponify triglycerides and form an equivalent amount of soaps is most unlikely.…”
Section: Interesterificationmentioning
confidence: 99%